Legal Protection of Persons with Disabilities as a Management of Guarantee on Human Rights - Leni Dwi Nurmala; Rustam Hs. Akili (Faculty of Law, Musamus University, 2022)
Human rights are universal and fundamental to all human beings. Human rights are rights that are inherent in the human person since birth that are used to maintain their dignity and human values. These rights must be believed to be gifts or gifts from God Almighty which no one has the right to rob, remove or revoke these rights. In Indonesia, with a very high population, the existence of persons with disabilities cannot be denied. Disability can occur due to health problems that arise from birth, chronic or acute illnesses, and injuries that can be caused by accidents, wars, riots, disasters, and so on. Persons with disabilities make us realize that they are human beings who are given physical deficiencies, but are not different people. The existence of persons with disabilities is a minority who must receive guarantees for their survival. In Indonesia, persons with disabilities have been given legal protection, namely the promulgation of Law no. 8 of 2016 concerning Persons with Disabilities which provides legal protection for persons with disabilities, but is still not fully able to fulfill the basic rights of persons with disabilities, including the right to legal protection, the right to obtain decent work, the right to education and so on. For this reason, this paper aims to find out about how legal protection is given to persons with disabilities in Indonesia.